Pengaruh Kode Etik Auditor Dan Kualitas Audit Terhadap Kualitas Laporan Keuangan - Siringoringo, Zesen; Pangaribuan, Hisar (Lembaga Riset Ilmiah, 2022)
The purpose of this study was to determine the effect of the Code of Ethics and the Quality of Auditing on the Quality of Financial Reporting. The target of this research is an Accounting Firm based on Java Island with a total sample of 117. The data collection method is a research method for direct opinions from accountants and this research data uses the SPSS application a process version 25.0. Test in this study used descriptive statistical tests, classical acceptance test ( normality test, multiple colinearity, and heterogeneity), and hypothesis testing (F test and T-test). The results of this study indicate that the audit code of ethics has a significant effect on the quality of auditors’ financial statements, which is very important in efforts to improve the quality of financial reporting and other results. It does not affect the quality of the report significantly